THE FORMATION OF JUNIOR STUDENTS' LEXICAL COMPETENCE BY MEANS OF WORD-FORMATION - Наталія Сіранчук (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article describes the efficiency of junior students' lexical competence development by means of word-formation which is direcedt on enriching passive and active vocabular of the studentsy. The main ways of lexical competence development of junior students by means of word-formation are highlighted in the article. the principal factors that help to learn the lexical items are described. The factors which facilitate the interpretation of derived lexical items are emphasized. Conditions which influence the effectiveness of word-formation analysis in primary school are indicated. Knowledge and students' skills that are required for development of lexical competence by means of word-formation are selected. The essential feature of experimental technique (the constant attention to the contet and functions of morphemes) are specified.